Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

What is 6a squared - 12a+36

Sagot :

6a²-12a+36= 6a²-12a=-36  
Put the normal number on the other side to have the variables on one side, and the normal number on the other.
Then group:
                = 36a-12a= -36
                = 24a=-36
Then isolate a:
                = a=-36/24
Then simplify:
                =a = - 3/2

Hope this helps!


6a² - 12a + 36 = 0
a = -(-12) +/- √((-12)² - 4(6)(36))
                        2(6)
a = 12 +/- √(144 - 864)
                    12
a = 12 +/- -√720
           12
a = 12 +/- -√(9 × 16 × 5)
                   12
a = 12 +/- -√9 -√16 -√5
                   12
a = 12 +/- (-3)(-4) -√5
                 12
a = 12 +/- 12-√5
              12
a = 12 +/- 12(-2.236067978)
                      12
a = 12 +/- (-26.83281573)
                     12
a = 12 + (-26.83281573)            a = 12 - (26.83281573)
                    12                                              12
a = 12 - 26.83281573                a = 12 + 26.83281573
                   12                                              12
a = -14.83281573                      a = 38.832815723
               12                                                12
-1.236067978                            a = 3.236067978